S100A2 induces epithelial–mesenchymal transition and metastasis in pancreatic cancer by coordinating transforming growth factor β signaling in SMAD4-dependent manner - Qinbo Chen; Hangcheng Guo; Haojie Jiang; Zujian Hu; Xuejia Yang; Ziwei Yuan; Yuanyuan Gao; Ge Zhang; Yongheng Bai (Cell Death Discovery, 2023)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive tumor and is associated with a poor prognosis. Treatment strategies for PDAC are largely ineffective primarily because of delay in its diagnosis and limited efficacy of systematic treatment. S100A2 is associated with the proliferation, migration, and differentiation of several tumors; however, its effects on PDAC and the associated molecular mechanisms remain to be explored. We studied the mechanisms underlying the effect of S100A2 on epithelial–mesenchymal transition (EMT) and metastasis in PDAC cells. We found that the level of S100A2 remarkably increased and was associated with poor PDAC prognosis. The overexpression of S100A2 in PANC-1 cells also induced EMT, in addition to increasing the invasion and migration of PDAC cells, whereas the knockdown of S100A2 markedly inhibited cell metastasis. Furthermore, S100A2 was found to enhance metastatic abilities in vivo. The overexpression of S100A2 increased SMAD4 expression, whereas the knockdown of S100A2 reduced SMAD4 expression. SMAD4 overexpression could effectively rescue the effects of S100A2 knockdown on EMT. S100A2 mechanistically activated the transforming growth factor (TGF)-β/Smad2/3 signaling pathway, upregulated SMAD4 expression, induced EMT, and increased PANC-1 cell metastasis. In conclusion, the S100A2/SMAD4 axis modulates EMT to accelerate PDAC development. Our results supplement and enrich the understanding of the pathogenesis underlying PDAC and provide a new theoretical basis and strategy targeting S100A2 for the diagnosis and treatment of PDAC.